How to locate the fistula orifice of spinal extradural arachnoid cyst: Surgical experience and clinical outcome - Yu Tian; Yong Chen; Long Chen; Xianghong Meng; Mengmeng Fu; Xin Shi; Yuanxiang Lin (BMC Surgery, 2023)
Abstract Background In clinical practice, spinal extradural arachnoid cysts (SEAC) are relatively rare. The key to the treatment of SEAC is recognize and close the dural defects (fistula orifice), but there is currently no convenient method to locate and identify the fistula. We propose a method for predicting the location of lumbar/thoracolumbar SEAC fistula based on surgical experience, subsequently closing the fistula through posterior unilateral interlaminar fenestration. Evaluating its surgical efficacy and investigated its effect on patient prognosis. Methods A stepped approach based on clinical experience is proposed. A retrospective analysis was performed on 6 patients diagnosed with thoracolumbar SEAC disease and treated with posterior unilateral interlaminar fenestration through the position by pre-estimated fistula orifice in our hospital’s Department of Neurosurgery between January 2017 and January 2022. Results All patients who received this treatment experienced significantly lower postoperative VAS pain scores and ODI index compared to their corresponding preoperative values (P < 0.01). During the ongoing follow-up after surgery, no unstable vertebral column, adverse effects, or complications were reported. Conclusions The use of posterior unilateral interlaminar fenestration for the treatment of large SEAC in the adult lumbar/thoracolumbar segment can reduce spinal cord manipulation and enhance spine stability. The disease can be treated by sealing the fistula orifice through a small fenestra, the position of which is assessed before surgery. This surgical method reduces trauma and improves the prognosis of patients with large SEAC.